2019
DOI: 10.1002/mp.13907
|View full text |Cite
|
Sign up to set email alerts
|

LDeform: Longitudinal deformation analysis for adaptive radiotherapy of lung cancer

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In lung cancer, various studies have utilized Jacobian maps using CT or PET/CT to assess lung volumetric shrinkage, 20 detect lung radiation‐induced disease, 21 visually identify temporal changes in lung nodules, 22 and correlate Jacobian map features and histopathologic response 23 . A recent study proposed a method to quantify surface changes of the tumor to predict tumor geometrical responses 24 . Similarly, Zhang et al 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In lung cancer, various studies have utilized Jacobian maps using CT or PET/CT to assess lung volumetric shrinkage, 20 detect lung radiation‐induced disease, 21 visually identify temporal changes in lung nodules, 22 and correlate Jacobian map features and histopathologic response 23 . A recent study proposed a method to quantify surface changes of the tumor to predict tumor geometrical responses 24 . Similarly, Zhang et al 25 .…”
Section: Discussionmentioning
confidence: 99%
“…23 A recent study proposed a method to quantify surface changes of the tumor to predict tumor geometrical responses. 24 Similarly, Zhang et al 25 cross-validated and expanded the predictive atlas to estimate geometric patterns of lung shrinkage using data from two institutions. These works focused on the visible tumor or its boundaries (surface) and do not aim at distinguishing or accounting for modes of tumor regression, that is, elastic versus non-elastic regression.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…While other studies have also identified pulmonary toxicities as predictors of DIR inaccuracy (48), the algorithms are continuously being improved to account for such changes and presence of similar conditions (49)(50)(51)(52), and even moving towards accurately predicting tumor responses (53). While utilizing DIR algorithms with CBCT imaging is a promising solution to a full re-simulation, not all treatment modalities allow for daily CBCT imaging.…”
Section: Use Of Deformable Image Registration Based Algorithms In Place Of Re-simulationmentioning
confidence: 99%
“…According to retrospective studies, the setup variation can be characterized early on during the treatment process 5,12 . Therefore, ART may potentially benefit from predictions of patient's anatomical deformation in the later timepoints since these predictions could directly be used in the replanning process and improve the therapeutic outcome 10,13,14 . In this paper, we present a novel 3D deep learning sequence‐to‐sequence model (Seq2Seq) using ConvLSTM to predict patient anatomy deformation (with reference to the planning/pre‐treatment image) given any number of input/output sequence timepoints.…”
Section: Introduction and Purposementioning
confidence: 99%